BEST PRACTICE PENGEMBANGAN MUTU SMK TERPADU LAMPANG SUBANG - Asep Priatna (Jurnal Administrasi Pendidikan, 2019)
This study aims to reveal the efforts and results that have been achieved by Lampang Subang Integrated Private Vocational Schools in improving the quality of learning to meet national education standards (SNP), so that they become private schools with the status of national standard schools (SSN). This research is a survey research with a quantitative approach. The study was conducted at the Integrated Vocational School of Lampang Subang, West Java. The results showed that the level of achievement of the program that had been compiled in the RPS of Lampang Integrated Vocational School had reached 90% with the main target being the achievement of the UAN level and graduation that had been carried out by teachers both in the preparation of RPPs and teaching materials had reached 85%, Management developed by Integrated Vocational Schools Long-time contributed significant value, especially in program planning and implementation, while the supervision and leadership of the Principal has been running well, so the value obtained is quite significant, while other components that are quite prominent are PBM and content standards that get good enough grades , so that it can be developed further